Causes and consequences of intratumoral cellular heterogeneity and the role of the melatonergic system in brain tumors - Kinker, Gabriela Sarti (2019)
Tumor cell plasticity and heterogeneity are key features underlying disease progression and therapeutic resistance. Recent advances of single-cell RNA-seq (scRNA-seq) technologies have highlighted the co-existence of transcriptionally distinct subpopulations of malignant cells within single tumors of different lineages. Thus, there is now a need to establish frameworks to better understand the biological and clinical relevance of such cellular diversity, as well as its underlying molecular mechanisms. To address this issue, we generated scRNA-seq data for 198 cell lines (22 cancer types) and systematically characterized intra-cell line expression heterogeneity. We found that co-existence of highly distinct subpopulations within the same cell line is rare, while continuous patterns of expression heterogeneity, represented by spectra of cellular states are common, recur across different cell lines, are associated with multiple biological process, and are usually independent of genetic diversity. Notably, despite the absence of a native and spatially-variable microenvironment in vitro, many of the continuous programs observed in cell lines recapitulate those found in clinical samples, suggesting a prominent role of intrinsic epigenetic plasticity in generating intratumoral heterogeneity. The data also allowed us to prioritize specific cell lines as model systems of cellular plasticity. As an example, we selected two of such models to demonstrate the temporal dynamics and vulnerabilities associated with a cancer senescence program observed both in cell lines and in human tumors. Additionally, given the means by which malignant cells communicate in the tumor bulk, i.e. physical cell-to-cell interactions and secretion of soluble factors, we also aimed to explore new autocrine/paracrine signaling networks that could be exploited clinically. Melatonin, best known as the \"pineal hormone\", is a pleiotropic molecule produced by many extrapineal tissues and increasingly recognized as a tumor suppressor agent. Melatonin acts through several biological mechanisms, including direct scavenging of free radicals and activation of high-affinity G-protein coupled receptors (MT1 and MT2). Over the past decade, our group has provided compelling evidences that fine-tuning the extrapineal production of melatonin during acute inflammation is critical for the maintenance of tissue homeostasis. However, our knowledge about the pathophysiological role of local melatonin in malignant processes is very limited. Interestingly, here we demonstrated that the ability of gliomas to synthesize and accumulate melatonin negatively correlates with their overall malignancy. Using gene expression data, we designed a predictive model of the content of melatonin in the tumor microenvironment, the ASMT:CYP1B1 index, which was shown to be a positive prognostic factor, independent of glioma grade and histological subtype. Finally, as we sought to provide further support for the rational use of melatonin and analogous in brain cancer therapy, we demonstrated that in gliomas and medulloblastomas MT1 and MT2 melatonin receptors play opposite roles in disease progression. Remarkably, compounds that simultaneously activate MT1 and inhibit MT2 displayed a robust antitumor effect in vitro and in vivo, highlighting the potential of such receptors as therapeutic targets